1997
DOI: 10.1101/gad.11.23.3242
|View full text |Cite
|
Sign up to set email alerts
|

Organizing a functional junctional complex requires specific domains of the Drosophila MAGUK Discs large

Abstract: Discs large (Dlg) was the first identified member of an increasingly important class of proteins called membrane-associated guanylate kinase homologs (MAGUKs), which are often concentrated at cell junctions and contain distinct peptide domains named PDZ1-3, SH3, HOOK, and GUK. Dlg is localized at and required for the formation of both septate junctions in epithelial cells and synaptic junctions in neurons. In the absence of Dlg, epithelia lose their organization and overgrow. We tested the functions of each do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
130
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 52 publications
13
130
3
Order By: Relevance
“…This ®nding is consistent with studies on Drosophila dlg showing that the GUK domain and the amino-terminal region containing the PDZ domains are required for the tumor suppressor function of dlg (Woods and Bryant, 1991;Woods et al, 1996). Furthermore, in studies using transgenic¯ies, it was shown that the second and third PDZ domains, the SH3 domain, and a region between the SH3 and GUK domains called the HOOK domain are all required for rescue of the overgrowth phenotype of imaginal disc epithelium in dlg-null larvae (Hough et al, 1997). Since the PDZ, SH3 and GUK domains are believed to constitute protein-interaction interfaces, structural alterations in these domains may abrogate the ability of hDLG to interact with key regulatory or e ector molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ®nding is consistent with studies on Drosophila dlg showing that the GUK domain and the amino-terminal region containing the PDZ domains are required for the tumor suppressor function of dlg (Woods and Bryant, 1991;Woods et al, 1996). Furthermore, in studies using transgenic¯ies, it was shown that the second and third PDZ domains, the SH3 domain, and a region between the SH3 and GUK domains called the HOOK domain are all required for rescue of the overgrowth phenotype of imaginal disc epithelium in dlg-null larvae (Hough et al, 1997). Since the PDZ, SH3 and GUK domains are believed to constitute protein-interaction interfaces, structural alterations in these domains may abrogate the ability of hDLG to interact with key regulatory or e ector molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Since the PDZ, SH3 and GUK domains are believed to constitute protein-interaction interfaces, structural alterations in these domains may abrogate the ability of hDLG to interact with key regulatory or e ector molecules. In addition, the HOOK domain and the second PDZ domain have been shown to be important for the correct localization of some proteins at the membrane and at the septate junction, respectively (Hough et al, 1997). It is also well known that MAGUKs are involved in the clustering of membrane proteins (Kornau et al, 1995;Kim et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, structure-function analyses of nTSG proteins suggest that polarity and proliferation control are to some extent separable, with distinct regions of the multidomain Dlg and Scrib proteins contributing to the two functions (Hough et al 1997;J. Zeitler, C. Hsu, and D. Bilder, unpubl.).…”
Section: Polarity and Proliferation Control: Modelsmentioning
confidence: 99%
“…Studies in Drosophila, C. elegans and mammalian epithelial cells have demonstrated that apical/basal cell polarity is created through membrane domains and junctional complexes with characteristic positions along the apical/basal axis (Bryant, 1997). In vertebrates, these are the tight junctions, adherens junctions and a basolateral domain, from apical to basal, respectively.…”
Section: Introductionmentioning
confidence: 99%